Comparison of inventory management methods: reliability centered spares (RCS), ABC analysis and fixed timed period - Manalu, Iuskus Kiadi; Firmansyah, Choirul; Fadly Syam, Muhammad; Syamil, Ahmad (Institute of Computer Science (IOCS), 2024)
Spare parts inventory management is very important for PT XYZ, which is one of the largest fertilizer producers in Indonesia. The cost of spare parts, especially for air compressors, constitutes a significant portion of the production cycle cost. This study aims to determine the optimal spare parts inventory value at PT XYZ by comparing the ABC analysis, fixed-time period, and reliability-centered spares (RCS) methods. The results showed that the fixed-time period method has a positive impact on company profits of Rp. 1,648,391,080 and offers better control of Class A spare parts inventory. The ABC analysis method also helps prevent inventory shortages that could disrupt company operations. However, the RCS method cannot be compared because the probability value must be determined by the company itself. In this study, demand fluctuations, lead time, reorder points, and inventory levels are also crucial considerations in determining the value of spare parts inventory. By using the fixed-time period method, PT XYZ can achieve greater profits and effectively control its spare parts inventory